1997
DOI: 10.1038/sj.bjp.0701451
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of α1‐adrenoceptor subtypes mediating vasoconstriction in rabbit cutaneous resistance arteries

Abstract: 1 Cutaneous resistance arteries (c.r.a.) (internal diameter=240.94+5.42 mm, n=67/25 (number arteries/number animals)) from New Zealand white rabbits were mounted in wire myographs and a normalization procedure followed. 2 Cumulative concentration-response curves (CCRCs) were constructed for the a-adrenoceptor agonists noradrenaline (NA), (R)A61603 and phenylephrine (PE) in the presence of cocaine (3 mM), propranolol (1 mM) and corticosterone (10 mM). The eects of competitive a 1 -adrenoceptor antagonists, praz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 36 publications
0
23
1
Order By: Relevance
“…Whereas cardiac adrenergic drive initially supports the performance of the failing heart, long-term activation of the sympathetic nervous system exerts deleterious effects that can be antagonized by the use of beta blockers. Sympathetic activation can increase ventricular volumes and pressure by causing peripheral vasoconstriction 336 and by impairing sodium excretion by the kidneys. 337 Norepinephrine can also induce cardiac hypertrophy but restrict the ability of the coronary arteries to supply blood to the thickened ventricular wall, leading to myocardial ischemia.…”
Section: Beta-adrenergic Receptormentioning
confidence: 99%
“…Whereas cardiac adrenergic drive initially supports the performance of the failing heart, long-term activation of the sympathetic nervous system exerts deleterious effects that can be antagonized by the use of beta blockers. Sympathetic activation can increase ventricular volumes and pressure by causing peripheral vasoconstriction 336 and by impairing sodium excretion by the kidneys. 337 Norepinephrine can also induce cardiac hypertrophy but restrict the ability of the coronary arteries to supply blood to the thickened ventricular wall, leading to myocardial ischemia.…”
Section: Beta-adrenergic Receptormentioning
confidence: 99%
“…Finally, by stimulating growth and oxidative stress in terminally differentiated cells, norepinephrine can trigger programmed cell death or apoptosis (254). These deleterious effects are mediated through actions on alpha-1-, beta-1-, and beta-2-adrenergic receptors (138,215,(247)(248)(249)(250)(251)(252)(253)(254).…”
Section: Practical Use Of Beta-blockers Selection Of Patientsmentioning
confidence: 99%
“…Whereas cardiac adrenergic drive initially supports the performance of the failing heart, long-term activation of the sympathetic nervous system exerts deleterious effects that can be antagonized by the use of beta-blockers. Sympathetic activation can increase ventricular volumes and pressure by causing peripheral vasoconstriction (247) and by impairing sodium excretion by the kidneys (248). Norepinephrine can also induce cardiac hypertrophy but restrict the ability of the coronary arteries to supply blood to the thickened ventricular wall, leading to myocardial ischemia (215,249,250).…”
Section: Practical Use Of Beta-blockers Selection Of Patientsmentioning
confidence: 99%
“…Contractions are reported to be mediated at least partly by α 1Β -adrenoceptors in a number of tissues: rabbit corpus cavernosum [104] and rabbit cutaneous resistance arteries [123]. In studies of blood vessels from adrenoceptor KO mice, it was found that the major subtypes involved in contractions are α 1A and α 1D , but that the α 1Β -adrenoceptor plays a minor but clearly defined role in contractions in aorta, carotid, mesenteric and tail arteries [28].…”
Section: Vascular Responses Mediated By α 1b -Adrenoceptorsmentioning
confidence: 98%
“…WT wild type. (Taken from Bexis and Docherty, unpublished) guinea pig aorta, [101], rabbit cutaneous resistance arteries [123] and rat small mesenteric artery [137] were reported to contain α 1L -adrenoceptors.…”
Section: Vascular Responses Mediated By α 1a -Adrenoceptorsmentioning
confidence: 99%